Penyelesaian Kasus Perselingkuhan Melalui Sanksi Pidana Adat Di Kecamatan Pulau Wetang - Petrus Ricardo Jotley; Elsa Rina Maya Toule; Sherly Adam (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2022)
The purpose in writing this is an affair that occurs either between a husband and wife of another person or between a husband or wife and another man or woman outside of the husband and wife relationship. This research is a normative juridical research on this problem and then examines and knows the answers to this problem through a concept approach, statutory approach and case approach then from the results of the description conclusions and suggestions can be drawn. The results of the study show that the form of settlement of cases of infidelity/adultery through customary fines is carried out by means of requests for accountability to men to marry girls or wives of people who commit adultery/adultery, if they do not fulfill requests to marry other people's girls or wives then they are obliged to do so. payment of customary fines to the girl or wife of the person who has been harmed as well as the form of customary fines which are intended as customary sanctions in the form of two gold moons the size of a palm, one basta, animal/livestock, cows and Completion of customary fines in cases of infidelity/adultery through customary criminal sanctions in Pulau Wetang District are not appropriate and positive law is not recognized, because the act of damaging property precedes the existence of a customary settlement which has received criticism and rejection from the local indigenous people to the Village Government and Saniri Negeri. The settlement of adultery or extramarital affairs should only be done through traditional forums by following the provisions of customary fines decided at the Saniri customary assembly, not by destroying the property of the parties who have committed adultery or adultery.